Pattern of bone generation after irradiation in vascularized tissue engineered constructs - Eweida, Ahmad; Fathi, Ibrahim; Eltawila, Ahmed M.; Elsherif, Ahmad M.; Elkerm, Yasser; Harhaus-Wähner, Leila; Kneser, Ulrich; Sakr, Mahmoud F. (Journal of reconstructive microsurgery, 2018)
Background: Regenerative medicine modalities provide promising alternatives to conventional reconstruction techniques but are still deficient after malignant tumor excision or irradiation due to defective vascularization. Methods: We investigated the pattern of bone formation in axially vascularized tissue engineering constructs (AVTECs) after irradiation in a study that mimics the clinical scenario after head and neck cancer. Heterotopic bone generation was induced in a subcutaneously implanted AVTEC in the thigh of six male New Zealand rabbits. The tissue construct was made up of Nanobone (Artoss GmbH; Rostock, Germany) granules mixed with autogenous bone marrow and 80 μL of bone morphogenic protein-2 at a concentration of 1.5 μg/μL. An arteriovenous loop was created microsurgically between the saphenous vessels and implanted in the core of the construct to induce axial vascularization. The constructs were subjected to external beam irradiation on postoperative day 20 with a single dose of 15 Gy. The constructs were removed 20 days after irradiation and subjected to histological and immunohistochemical analysis for vascularization, bone formation, apoptosis, and cellular proliferation. Results: The vascularized constructs showed homogenous vascularization and bone formation both in their central and peripheral regions. Although vascularity, proliferation, and apoptosis were similar between central and peripheral regions of the constructs, significantly more bone was formed in the central regions of the constructs. Conclusion: The study shows for the first time the pattern of bone formation in AVTECs after irradiation using doses comparable to those applied after head and neck cancer. Axial vascularization probably enhances the osteoinductive properties in the central regions of AVTECs after irradiation.